2017
DOI: 10.1158/1541-7786.mcr-16-0234
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Loss-of-Function Screen Identifies SLC26A2 as a Novel Mediator of TRAIL Resistance

Abstract: TNF-related apoptosis inducing ligand (TRAIL) is a potent death-inducing ligand that mediates apoptosis through the extrinsic pathway and serves as an important endogenous tumor suppressor mechanism. Because tumor cells are often killed by TRAIL and normal cells are not, drugs that activate the TRAIL pathway have been thought to have potential clinical value. However, to date, most TRAIL-related clinical trials have largely failed due to the tumor cells having intrinsic or acquired resistance to TRAIL-induced … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Lines of evidence have revealed potential roles of SLC26A2 in the pathogenesis of primary aldosteronism and development of ulcerative colitis and Crohn's disease and colon cancer, and even dtd mice showed abnormal aldosterone secretion, thereby justifying its ubiquitous non-skeletal expression [ [57] , [58] , [59] , [60] , [61] ]. Importantly, SLC26A2 is also expressed in cytotrophoblasts and considered to facilitate maternal-to-fetal delivery of sulfate [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lines of evidence have revealed potential roles of SLC26A2 in the pathogenesis of primary aldosteronism and development of ulcerative colitis and Crohn's disease and colon cancer, and even dtd mice showed abnormal aldosterone secretion, thereby justifying its ubiquitous non-skeletal expression [ [57] , [58] , [59] , [60] , [61] ]. Importantly, SLC26A2 is also expressed in cytotrophoblasts and considered to facilitate maternal-to-fetal delivery of sulfate [ 62 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Our finding that vanadiumcontaining compounds selectively kill cancer cells expressing high levels of the sulfate transporter SLC26A2 was also surprising, given that a mechanistic link between the two had not been previously suspected. A recent study showed that SLC26A2 expression is a mechanism of resistance to TNF-related apoptosis-inducing ligandinduced cell death 38 ; it remains to be determined whether that mechanism is relevant to vanadium-induced killing and whether these compounds dysregulate sulfate homeostasis. Perhaps most interesting was our observation that the drug tepoxalin has the unique ability to inhibit cells that express high levels of the multidrug resistance gene ABCB1.…”
Section: Discussionmentioning
confidence: 99%
“…3.10. Col2a1-Cre; slc26a2 fl/fl mice recapitulate the phenotype of slc26a2 −/− mice Lines of evidence have revealed potential roles of SLC26A2 in the pathogenesis of primary aldosteronism and development of ulcerative colitis and Crohn's disease and colon cancer, and even dtd mice showed abnormal aldosterone secretion, thereby justifying its ubiquitous nonskeletal expression [57][58][59][60][61]. Importantly, SLC26A2 is also expressed in cytotrophoblasts and considered to facilitate maternal-to-fetal delivery of sulfate [62,63].…”
Section: Targeting Fgfr3 Signaling Modulates Cartilage Growth In Vitromentioning
confidence: 98%